2021
DOI: 10.1177/21582440211016841
|View full text |Cite
|
Sign up to set email alerts
|

Digital Reading and the Concept of Ebook: Metaphorical Analysis of Preservice Teachers’ Perceptions Regarding the Concept of Ebook

Abstract: The aim of this study was to determine the metaphorical perceptions of preservice Turkish teachers (PTTs) regarding the concept of ebook. In accordance with this aim, answers to the questions of “What are the metaphors used by PTTs for the concept of e-book?” and “Under which categories could the metaphors used by PTTs for the concept of e-book be collected?” were sought. A total of 150 preservice teachers studying in the Faculty of Education, Turkish Education Department at Çukurova University, constituted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
2
6
0
3
Order By: Relevance
“…These findings are consistent with the literature that reports that interactive e-book technologies support active learning as explained by the Cognitive Theory of Multimedia Learning (Bozkurt & Bozkaya, 2015;Buzzetto-More, 2015;Ciampa, 2012;Y. Huang et al, 2012;Karakoç Öztürk, 2021;Rockinson-Szapkiw et al, 2013); save learners money (Curry, 2021;Griffiths et al, 2018); are perceived favorably (Baron et al, 2017;Wook et al, 2014); and can positively reinforce student learning and improve learner outcomes (Asrowi et al, 2019;Buzzetto-More & Ukoha, 2009;Y. Huang et al, 2012;Karakoç Öztürk, 2021;Schwan & Riempp, 2004;Tung & Deng, 2006).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These findings are consistent with the literature that reports that interactive e-book technologies support active learning as explained by the Cognitive Theory of Multimedia Learning (Bozkurt & Bozkaya, 2015;Buzzetto-More, 2015;Ciampa, 2012;Y. Huang et al, 2012;Karakoç Öztürk, 2021;Rockinson-Szapkiw et al, 2013); save learners money (Curry, 2021;Griffiths et al, 2018); are perceived favorably (Baron et al, 2017;Wook et al, 2014); and can positively reinforce student learning and improve learner outcomes (Asrowi et al, 2019;Buzzetto-More & Ukoha, 2009;Y. Huang et al, 2012;Karakoç Öztürk, 2021;Schwan & Riempp, 2004;Tung & Deng, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…When compared with the broader body of literature, these findings are also consistent with multiple prior studies that have found that interactive e-book technologies can reinforce student learning, assist with assignments, help students develop confidence about the subject matter, and provides students with meaningful feedback (Asrowi et al, 2019;Y. Huang et al, 2012;Karakoç Öztürk, 2021;Schwan & Riempp, 2004;Tung & Deng, 2006).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…An e-book or electronic book is a form of electronic text published digitally. This new digital literacy is becoming more accessible as people use e-book applications with various portable devices, such as tablets, i-pads and other e-book readers (Karakoç Öztürk, 2021). E-Book 3 dimensions were developed to help convey information more efficiently, interestingly, and limited in space and time (Alwan, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%